Estudio sobre el uso de computador y el reconocimiento de la existencia de internet en una población vulnerable del caribe Colombiano (2011)
This paper presents the results of a research on Information and Communication Technology -ICT; it specifically focuses on computer use and knowledge of the Internet existence by vulnerable population. La Escuela Busca al Niño (EBN-Santa Marta) Project was selected as a context of research. This was operated by Universidad del Magdalena and was supported by Ministry of National Education, UNICEF, ECOPETROL and Santa Marta Council. The project aim was to provide care for children and adolescents in vulnerable conditions, outside the education system, and their families. In this study, a characterization of 2481 persons of family cores beneficiaries of project was done. The results showed that access levels to computers and knowledge of Internet existence was very low, highlighting that 94% of the population under study has not access to a computer and do not know about Internet existence.